Avaliação da distribuição das tensões em prótese do tipo “All on Four”: estudo pelo método dos elementos finitos tridimensionais - Amoroso, Andressa Paschoal [UNESP] (2013)
The increasing and continuous demand for implants prosthetic rehabilitation along with the proven success of dental implants make that search for means which can further strengthen this type of treatment is abundant, especially regarding the distribution of forces. Purpose: The aim of this study was to analyze the stress distribution generated in different configurations of the full-arch implant-supported prostheses, through the three-dimensional finite element method. Material and method: For this study two mandibular models were made using the graphical modeling program SolidWorks 2010 (SolidWorks Corp., Massachusetts, USA) and Rhinoceros® 3D 4.0 (NURBS Modeling for Windows, EUA). Each model represented a jaw with a full-arch implant-supported prosthesis using external hexagon implants with 4.0 x 13.0 mm (Master Connection Implant Systems Ltda., São Paulo, Brazil) located in the interforaminal region, varying the inclination. Model 1: prosthesis with 4 implants arranged perpendicularly to the ridge crest and model 2: All-on-four prosthesis (distal implants tilted at 30 °). The representation of the prosthesis was with acrylic resin and the metallic infrastructure with NiCr. The three-dimensional images were exported to finite element programs FEMAP 11.0 for mesh generation. The axial load applied was 300N, being 75N bilateral in each tooth, and oblique of 150N, being 75N unilateral in each tooth, in 1st premolars and 1st molars. Results: After analysis at the program NEiNastran® 9.2 (Noran Engineering, Inc., EUA), the results were visualized through individualized maps of von Mises stress and main maximum stress on each model. It can be observed in the model with tilted implants, that for both loads the stress concentrations were higher. Conclusion: It was concluded that the All on four prostheses presented highest stress concentrations, especially in the region of the distal implant.